Quantum Chemical Study of Arsenic (III, V) Adsorption on Mn-Oxides: Implications for Arsenic(III) Oxidation - Zhu, Mengqiang; Paul, Kristian W; Kubicki, James D; Sparks, Donald L (Environmental science & technology, 2009)
Density functional theory (DFT) calculations were used to investigate As(V) and As(III) surface complex structures and reaction energies on both Mn(III) and Mn(IV) sites in an attempt to better understand As(III) oxidation by birnessite, a layered Mn-dioxide mineral. Edge-sharing dioctahedral Mn(III) and Mn(IV) clusters with different combinations of surface functional groups (>MnOH and >MnOH2) were employed to mimic pH variability. Results show that As(V) adsorption was more thermodynamically favorable than As(III) adsorption on both Mn(III) and Mn(IV) surface sites under simulated acidic pH conditions. Therefore, we propose that As(V) adsorption inhibits As(III) oxidation by blocking adsorption sites. Under simulated acidic pH conditions, Mn(IV) sites exhibited stronger adsorption affinity than Mn(III) sites for both As(III) and As(V). Overall, we hypothesize that Mn(III) sites are less reactive in terms of As(III) oxidation due to their lower affinity for As(III) adsorption, higher potential to be blocked by As(V) complexes, and slower electron transfer rates with adsorbed As(III). Results from this study offer an explanation regarding the experimental observations of Mn(III) accumulation on birnessite and the long residence time of As(III) adsorption complexes on manganite (r-MnOOH) during As(III) oxidation.